Strategy-Instruction and strategy clustering in the development of young learners' reading skills. (April 2021) - Razı, Özge; Grenfell, Michael James
Abstract: Past research has demonstrated the positive outcomes of Strategy-Instruction in reading tasks. However, most of it has been conducted outside of school contexts, for relatively short periods of time, and has predominantly used quantitative methods. There is little SI research extending over a school semester, embedded in regular school hours, and almost none focused on the use of strategy clusters. The importance of theoretical justification for the choice of strategies employed in research has also been overlooked (see Plonsky, 2019). This article reports on a quasi-experimental mixed-methods SI study, aimed at encouraging strategy-cluster use in a secondary school context. Strategy selection for the SI was based on a multifactor theory of second language literacy. The participants ( n = 119) were 12-year-old learners, with instruction taking place during their regular school time over one school semester. The quantitative data showed the success of SI. The qualitative data provided valuable insights into strategy clustering, strategy chains, and strategy-cluster-types. Analysis of the two data sources reinforces the links between strategy clusters and reading comprehension.